-2(5s+2)+5(s-3)=

Simple and best practice solution for -2(5s+2)+5(s-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5s+2)+5(s-3)= equation:


Simplifying
-2(5s + 2) + 5(s + -3) = 0

Reorder the terms:
-2(2 + 5s) + 5(s + -3) = 0
(2 * -2 + 5s * -2) + 5(s + -3) = 0
(-4 + -10s) + 5(s + -3) = 0

Reorder the terms:
-4 + -10s + 5(-3 + s) = 0
-4 + -10s + (-3 * 5 + s * 5) = 0
-4 + -10s + (-15 + 5s) = 0

Reorder the terms:
-4 + -15 + -10s + 5s = 0

Combine like terms: -4 + -15 = -19
-19 + -10s + 5s = 0

Combine like terms: -10s + 5s = -5s
-19 + -5s = 0

Solving
-19 + -5s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '19' to each side of the equation.
-19 + 19 + -5s = 0 + 19

Combine like terms: -19 + 19 = 0
0 + -5s = 0 + 19
-5s = 0 + 19

Combine like terms: 0 + 19 = 19
-5s = 19

Divide each side by '-5'.
s = -3.8

Simplifying
s = -3.8

See similar equations:

| 5x+3=8x+2 | | N/5-(-11)=9 | | 13.5(n)=189 | | 8-x/5=22 | | -11-12g=-71 | | 9(4-s)=10+45 | | 2(2)+3x=24 | | 40(n)=324 | | 34-8x=16+10x | | Y^2-2y+5-8y+10=0 | | 5(h-2)-6(h+1)= | | x+17+2x+1=90 | | 3(n)=210 | | -165=13a | | 17(b-4)= | | 200=x^3+4x^2+4x | | X-2=11/24 | | 22x-3=20+10x | | F/10-11=9 | | 18=9x-7 | | L=1+-3w | | 4(4x-4)=-144 | | 5(n)=126 | | 7+4(x-4)-10=-45 | | 3+3x=4x+20 | | 13=×/3-22 | | 50/X-60=51.666 | | 2x-15+3(x-1)=13 | | 2x+3(8)=24 | | 7x-7*2=49 | | y-5=-5.2(x+4) | | 3(n)=1200 |

Equations solver categories